Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences